Perovskite solar cells: Recent development and perspectives - Aleksić Katarina M.; Marković Smilja B. (Tehnika, 2022)
The energy conversion efficiency of hybrid organic-inorganic perovskite solar cells (PSCs) has reached a value comparable to commercially available silicon solar cells. The main challenges for their commercialization are instability and toxicity.